Perioperative complications and outcomes in children with cerebral palsy undergoing scoliosis surgery. Issue 10 (8th August 2016) - Bendon, Anju A.; George, Khristine A.; Patel, Davandra
Summary: Introduction: Neuromuscular scoliosis is a known risk factor for postoperative complications after corrective spine surgery. Few studies have looked at the preoperative factors affecting postoperative complications in children with cerebral palsy. Aim: The aim of this study was to examine the factors that might influence postoperative course in patients with cerebral palsy undergoing spine surgery for scoliosis. Methods: Nineteen case notes of children with cerebral palsy who had spine surgery (2008–2014) were reviewed retrospectively. Preoperative comorbidities and postoperative complications were noted and complications were classified as major and minor. Results: Thirteen out of 19 (68.4%) patients had two or more systemic comorbidities. Most common comorbidities included reflux and seizure disorder. Nine patients (49%) had at least one major complication. About 5/19 patients had respiratory complications requiring ventilation and 4/19 had massive blood loss. A higher incidence of postoperative major complication was recorded in the group with two systemic comorbidities as compared to those with less than two systemic comorbidities (47% vs 16%). Both patients who had a single‐stage anterior release and posterior fixation had a major complication. Conclusion: Presence of two or more comorbidities and thoracotomy are risk factors for perioperative complications in children with cerebral palsy undergoing surgery for scoliosis correction. Abstract :